DEFINITIVE INCOME DETERMINATIONS: THE MEASUREMENT OF CORPORATE INCOMES ON AN OBJECTIVE SCIENTIFIC BASIS. - Kelley, Arthur C. (The Accounting Review, 1948)
Abstract The basic concept in accounting, as in economics, is the concept of income, and accountants are supposed to be experts trained in the procedures of measuring the amount of income earned by or accrued to business enterprises during their fiscal periods. The chief reason for the present-day disagreement in the measurement of income for a given period does not lie in tile necessary use of subjective measurement for certain items of cost, but it does lie in the fact that the basic standards or principles on which the very concept of income rests are not agreed to and generally accepted. If this doctrine of definitive income determination were accepted generally by the profession, it would simplify and make more precise and objective the measurement of annual income. The earnings of American corporations are facts which are strongly affected with a public interest, and the amounts of these earnings have a definite bearing on social and governmental policies, on labor compensation, on taxes and on prices to the consumers. It does not seem to be an overstatement to say that accountancy can become a science once the basic concept of net income is precisely defined and measured in accord with generally accepted principles and standards.